Mass spectrometry (LC-MS-MS) as a tool in the maillard reaction optimisation and characterisation of new 6-methoxy-tetrahydro-β-carboline derivatives - Goh, T.B.; Mordi, M.M.; Mansor, S.M. (Universiti Kebangsaan Malaysia, 2015)
Four new 6-methoxy-tetrahydro-β-carboline derivatives (1-6- methoxy-1-phenyl-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole, 2-6-methoxy-1-(4-methoxyphenyl)-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole, 3-6-methoxy-1-methyl-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indole and 4-2-methoxy-4-(6-methoxy-2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indol-1-yl)phenol) were prepared via the Maillard reaction using 5-methoxytryptamine and various aldehydes in water. The synthesis reaction conditions were optimised in catalyst loading, temperature and time using LC-MS for optimum yields. Surface response methodology and contour plot was selected as an approach for optimisation. The optimum yield could be achieved below 50oC within 5 h at 7 mole % catalyst loading at yields > 70%. The β-carboline compounds produced were characterised using electrospray ionization mass spectrometry (ESI-MS) and electrospray tandem mass (ESI-MS/MS). The mass fragmentation patterns of this group of heterocyclic tetrahydro-ß-carboline compounds are described herein.